Benefit of veno-arterial extracorporeal membrane oxygenation combined with Impella (ECpella) therapy in acute coronary syndrome with cardiogenic shock. Issue 2 (August 2022) - Shibasaki, Ikuko; Masawa, Taito; Abe, Shichiro; Ogawa, Hironaga; Takei, Yusuke; Tezuka, Masahiro; Seki, Masahiro; Kato, Takashi; Watanabe, Ryo; Koshiji, Nobuo; Saitou, Shunsuke; Ogata, Kouji; et al.
Abstract: Background: Patients with acute coronary syndrome complicated with cardiogenic shock (ACS-CS) frequently require mechanical circulatory support. In addition to veno-arterial extracorporeal membrane oxygenation (VA-ECMO), use of the Impella® (ECpella) (Abiomed Inc., Danvers, MA, USA) heart pump may improve the prognosis of such patients. In this study, we compared the efficacy of VA-ECMO plus intra-aortic balloon pumping (ECMO-IABP) with that of the ECpella for add-on circulatory support of VA-ECMO. Methods: Clinical outcomes of 64 patients with ACS-CS treated with ECMO-IABP ( n  = 41) or ECpella ( n  = 23) between January 2013 and April 2021 were retrospectively analyzed. The primary outcomes were 30-day and 365-day mortality. In addition, patients resuscitated after cardiopulmonary arrest (CPA) were evaluated separately. Results: The ECpella group showed significantly lower mid-term mortality than the ECMO-IABP group [30-day mortality (39.1% vs 56.1%, respectively; p  = 0.193) and 365-day mortality (43.5% vs 75.6%, respectively; p  = 0.010)], with significantly higher rates of new hemodialysis and bleeding at the vascular access site. Also, among the limited number of patients resuscitated from CPA, mortality was significantly lower in the ECpella group than the ECMO-IABP group [30-day mortality (28.6% vs 65.4%, respectively; p  = 0.026) and 365-day mortality (28.6% vs 84.6%, respectively; p  < 0.001)]. Among the resuscitated patients, ECMO weaning period and the incidence of neurological complications were related to 30-day mortality; The incidence of neurological complications was related to 365-day mortality. The use of ECpella was strongly associated with both 30-day and 365-day survival. Conclusions: The ECpella heart pump may provide a survival advantage over ECMO-IABP in patients with ACS-CS. Graphical abstract: Unlabelled Image Highlights: Impella was more useful as an additional device for veno-arterial extracorporeal membrane oxygenation (VA-ECMO). ECpella (Impella+VA-ECMO) for patients with acute coronary syndrome combined with cardiogenic shock (ACS-CS). The use of ECpella was the strongest prognostic factor for ACS-CS. ECpella may be promising to treat with patients with ACS-CS.